WOMEN AS MANAGERS: ATTITUDES AND ATTRIBUTIONS FOR PERFORMANCE BY MEN AND WOMEN - Stevens, George E.; DeNisi, Angelo S. (Academy of Management Journal, 1980)
The article presents a replication of a study that investigated the relationships between attitudes towards women as managers. The study examines a number of attributions for the success and failure of women managers. Also discussed are a number of problems encountered by women who are attempting to gain access to male occupations. The article presents the influence of descriptions of success or failure of women managers to popular attitudes toward women as managers. The study is based on the assumption that these attitudes are stable and not situation specific.